High capacity cross layer optimization strategy for multi-hop wireless network with interference management - Lei SHI; Jiang-hong HAN; Yi SHI; Zhen-chun WEI (Tongxin xuebao)
A high-throughput cross-layer optimization strategy based on the interference management for the multi-hop multi-base-station wireless network environment was proposed.In the physical layer the successive interference cancella-tion was used to realize the interference management.In the up layers,first the Voronoi algorithm was used to achieve the zoning,second based on the min-hop algorithm,the initial link allocation and multi-hop routing scheme was established,third optimize the scheme based on the multi-time-slot allocating or multi-hop routing,and at last try to find a better strategy in each iteration.Theoretical analysis shows that the strategy has a polynomial time complexity,and the simula-tion results show that the entire network throughput has a 2 to 5 fold increase by using interference management.